2016
DOI: 10.1590/1980-5497201600010011
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalização por acidente vascular encefálico isquêmico no Brasil: estudo ecológico sobre possível impacto do Hiperdia

Abstract: Objective:The study evaluated the trend of hospitalization for ischemic stroke (HIS) and its hospital mortality in Brazil over the last 15 years as well as the impact of the Hiperdia program in this scenario. Methods: An ecological study was designed with analytical approach and data collected in the Hospital Admission System on episodes of stroke, over the years 1998 to 2012. All data were stratified by sex and age, creating an indicator for HIS and proportion of hospital mortality. To estimate the trend of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
9
0
14

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 35 publications
5
9
0
14
Order By: Relevance
“…According to the literature, with regard to sex, the incidence of stroke is higher in men (18) , a feature not observed in study because, in both years, the proportion of incidence of stroke, between the sexes was approximately 1:1, similar to the data observed in studies conducted in Brazil (13) , specifically in the Northeast (12) . Previous study, which found similar results in relation to sex and hospitalization for ischemic stroke, presented: "there is no need to elaborate strategies aimed at specific subpopulation of men and women in regard to adherence measures and behavior change" (13) .…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…According to the literature, with regard to sex, the incidence of stroke is higher in men (18) , a feature not observed in study because, in both years, the proportion of incidence of stroke, between the sexes was approximately 1:1, similar to the data observed in studies conducted in Brazil (13) , specifically in the Northeast (12) . Previous study, which found similar results in relation to sex and hospitalization for ischemic stroke, presented: "there is no need to elaborate strategies aimed at specific subpopulation of men and women in regard to adherence measures and behavior change" (13) .…”
Section: Discussionsupporting
confidence: 77%
“…Overall, the results showed a reduction in the number of hospitalizations from stroke between 2010 and 2014 confirming the trend of decline in the incidence of stroke in northeastern Brazil (12) mainly in Paraiba (13) , a trend observed since 2002 (12,13) . As regards the number of IHA by region, a higher concentration of hospitalization for stroke in municipalities outside João Pessoa MR, especially Patos, Campina Grande and Cajazeiras.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations